2022
DOI: 10.1002/pip.3569
|View full text |Cite
|
Sign up to set email alerts
|

Global prediction of the energy yields for hybrid perovskite/Si tandem and Si heterojunction single solar modules

Abstract: A strong expectation exists for a two-terminal hybrid perovskite/silicon tandem solar cell for generating substantially higher output power. Nevertheless, a high tandem cell efficiency under the standard condition does not guarantee high power generation in outdoor environment due to the requirement of current matching in a tandem device. Here, we predict the global energy yields of hybrid perovskite/Si tandem and Si heterojunction single modules by establishing a new rigorous self-consistent model that perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…This is consistent with the previous report which states that the lowest value of FF is located at the current matching point. [ 20,29 ] For bifacial tandem modules with other E g_PVK s, one also sees an increasing FF with rising current mismatch after increasing albedo (see Figure S9, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with the previous report which states that the lowest value of FF is located at the current matching point. [ 20,29 ] For bifacial tandem modules with other E g_PVK s, one also sees an increasing FF with rising current mismatch after increasing albedo (see Figure S9, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[16][17][18][19] After that, the climate-dependent EY of tandem modules on a global scale was investigated, which demonstrated that the monofacial tandem modules are more advantageous than SHJ modules in terms of EY. [20] Assuming comparable lifetime of PVK materials with that of c-Si cells, the LCOE of high-efficiency PVK/c-Si tandem modules is predicted more advantageous than that of single-junction c-Si modules. [21] In the previous work, the EY and related characteristics were mainly conducted for monofacial PV modules in which SHJ was typically used as the bottom cell.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the dependences of η SC and η STC on T cell are essential for evaluation of annual production. 31,45,46) Therefore, the explicit T cell dependence and T cell -dependent E g (dE dT g cell = 0.31 meV K -1 for PVK 47) and −0.27 meV K -1 for Si 48) ) in Eqs. (1)−(3) are involved, whereas η EQE , η ERE , and r s are approximated to be constant independent of T cell .…”
Section: Solar-to-electricity Energy Conversion Efficiency Of Tandem ...mentioning
confidence: 99%